2015
DOI: 10.1177/1078155215587345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender on capecitabine toxicity in colorectal cancer

Abstract: Female colorectal cancer patients experience a higher dose-limiting toxicity incidence than male patients when given adjuvant capecitabine dosed according to body surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
0
12
2
5
Order By: Relevance
“…The results also differ from numerous studies with cancer populations that did not find associations between sex and participation [46] or attrition [911]. An explanation may be provided by growing evidence for sex-based differences in response to anticancer treatments, showing that women experience higher incidence of toxicity and adverse reactions than men [40, 41]. It is possible that women in our sample experienced more treatment-related symptoms than men, which made them more likely to discontinue participation.…”
Section: Discussioncontrasting
confidence: 87%
“…The results also differ from numerous studies with cancer populations that did not find associations between sex and participation [46] or attrition [911]. An explanation may be provided by growing evidence for sex-based differences in response to anticancer treatments, showing that women experience higher incidence of toxicity and adverse reactions than men [40, 41]. It is possible that women in our sample experienced more treatment-related symptoms than men, which made them more likely to discontinue participation.…”
Section: Discussioncontrasting
confidence: 87%
“…Our study did not confirm some previously reported risks for cardiotoxicity, including age >55 years, female sex, use of platinum, hemoglobin levels, IHD, and common CVRF. 7 , 15 , 21 , 24 , 25 , 45-47 The proportion of patients with IHD in this study was higher in the cardiotoxicity group, but the difference was not significant, possibly because of the small number of patients and this aspect should be investigated in a larger group.…”
Section: Discussionmentioning
confidence: 60%
“…Because capecitabine is predominantly eliminated renally, it is contraindicated in patients with severe renal impairment (creatinine clearance below 30 mL/min). The incidence of grade 3 or 4 adverse events was higher in our study than in the overall population [23]. In patients with mild renal impairment no dosage reduction is required; however, it is plausible that renal dysfunction leads to higher capecitabine blood concentrations and greater toxicity, requiring dose adjustment.…”
Section: Discussionmentioning
confidence: 74%